HISTORICAL-THEORETICAL FOUNDATIONS OF THE FORMATION OF A CULTURE OF VALUABLE COMMUNICATION IN STUDENTS - Yuldashev Sodiq Norchayevich (American Journals, 2024)
This article presents the historical foundations of the formation of a value culture of communication among readers, a specific description of universal values and feedback from their scientists on the culture of communication in the course of historical development.The importance of value communication in the culture of personality and society, philosophical social aspects and value approaches are analyzed. The possibilities of forming a value culture of communication among students are considered.
Keywords: Education, science, value, communication, upbringing, kind word, decency, human maturity.